2020
DOI: 10.1186/s12877-019-1279-8
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Understanding the care and support needs of older people: a scoping review and categorisation using the WHO international classification of functioning, disability and health framework (ICF)

Abstract: Reference 1. Abdi, et al. Understanding the care and support needs of older people: a scoping review and categorisation using the WHO international classification of functioning, disability and health framework (ICF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 1 publication
2
28
0
Order By: Relevance
“…Addressing the unmet care and support needs of an ageing population, and designing services and solutions centred around what older people need and want, remains an urgent public health priority [ 37 ]. Previous large scale studies indicating that the level, maintenance and development of high quality social support networks contribute to positive QoL [ 38 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the unmet care and support needs of an ageing population, and designing services and solutions centred around what older people need and want, remains an urgent public health priority [ 37 ]. Previous large scale studies indicating that the level, maintenance and development of high quality social support networks contribute to positive QoL [ 38 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to demonstrate this relationship. Previous qualitative studies of older adults or family carers [ 37 , 52 , 56 ] have identified the impact of coordination of services, access to information and preventative strategies on clinical (e.g., physical function, medication management) and QoL outcomes. In Australia, due to maximum funding budgets for government-subsidised home care [ 57 ], individuals with higher needs may not be as well supported because of the limited number of available hours to address their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Each service outlet's expected score was obtained by taking the mean score of their clients' predicted values from the model, given their covariate values. The observed mean score was divided by the expected mean score and then multiplied by the study population mean score to obtain the risk-adjusted mean QoL score for each service outlet [37].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The abandonment of assistive technology can be due to both positive (e.g., improved health condition), and negative factors (e.g., poor usability design). Key issues relating to non-use of assistive technology include a lack of user involvement in the design and decision making process [30,[33][34][35], a lack of information about products and services [36][37][38] and the usability of assistive technology for the user [19,22,24,39]. The use of assistive technology varies amongst different groups.…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews identifying barriers to assistive technology use have tended to focus on specific health populations and groups: older adults, people with intellectual disabilities, spinal cord injuries, Alzheimer's, cognitive impairments, stroke [19,34,36,38,41,42]; specific types of assistive technology: mobility or devices for upper-limb rehabilitation [22,35], and specific environments such as assistive technology use in higher education [18]. However, our initial review of the literature suggested that many of the barriers to using assistive technology are common across multiple chronic conditions and devices.…”
Section: Introductionmentioning
confidence: 99%